Wildlife management practices in South Africa drive creation of hybrid zones - Benjamin-Fink, Nicole, author; Reilly, Brian, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Historically, wildlife translocations assisted in reestablishing species in areas of extinction and are currently employed in over 50 countries. Ironically, they may be responsible for the extinction of pure genetic lineages, thereby negatively impacting endangered, indigenous, and rare species worldwide. The need to intensely manage populations is accelerating and the use of translocation as a practice is rapidly utilized within the wildlife ranching industry. We hypothesize that black and blue wildebeest translocation practices are detrimental, likely to persist in their current form, and policies facilitate hybridization. 6,929translocated wildebeest from 275 private ranches and three provincial protected areas, across 5South African provinces, were documented over five years. We analysed dispersal patterns of two translocated species that hybridize: the endemic black wildebeest and the more common blue wildebeest, sustainability of the translocation practice (indicated by generated revenue), and links between policies and hybridization. Translocations facilitate hybridization by overlapping previously ecologically and geographically isolated species, from multiple origins. Key findings indicate that blue wildebeest males of reproductive age are primarily translocated, wildebeest are introduced to the private and commercial industry from multiple sources (1-34), generated revenue from wildebeest accounted for 20.8%, and spatial disconnectivity and separate feeding grounds are correlated with decreased hybridization. This raises concerns for ecological integrity, location of genetically pure populations, genetic swamping, and regulatory efficiency. We coin the concept of an Ecological Sustainable Network (ESN) certificate and propose transparent and accountable procedural frameworks that standardize wildlife translocation practices for wildlife managers in the game ranching industry
Wildlife management practices drives hybridization in South Africa: conservation implications
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.